(untitled) (Bangladesh Veterinarian, 2019)
Feed supplements were used up to 35 days in 240 Cobb-500 broilers divided randomly into four groups. The treatments were: control (basal diet; no additives), antibiotic (basal diet + antibiotic), probiotic (basal diet + protexin) and green tea (basal diet + 0.25% green tea powder). Body weight and body weight gain increased significantly (P<0.05) in the antibiotic, probiotic and green tea groups compared to the control. Lower (P<0.05) feed intake and better (P<0.05) feed conversion ratio occurred in the supplemented groups than the control group. Supplementation of antibiotic and green tea increased (P<0.05) crude protein content of the meat, while probiotic and green tea decreased (P<0.05) fat content compared to the control. Gizzard weight increased (P<0.05) in antibiotic group, whereas wing and caeca weight increased in green tea group. Supplemented groups had decreased (P<0.05) caecal microbial number compared to the control group. It is suggested that addition of probiotic and green tea improves growth parameters, composition of broiler meat and reduced microbial population. The Bangladesh Veterinarian (2018) 35(1&2): 13-24